Osteoblast-secreted WISP-1 promotes adherence of prostate cancer cells to bone via the VCAM-1/integrin α4β1 system. (10th July 2018) - Chang, An-Chen; Chen, Po-Chun; Lin, Yu-Feng; Su, Chen-Ming; Liu, Ju-Fang; Lin, Tien-Huang; Chuang, Show-Mei; Tang, Chih-Hsin
Abstract: Bone metastasis is a frequent occurrence in prostate cancer (PCa) that is associated with severe complications such as fracture, bone pain and hypercalcemia. The cross-talk between metastatic cancer cells and bone is critical to the development and progression of bone metastases. In our previous data, we have described how the involvement of the Wnt-induced secreted protein-1/vascular cell adhesion molecule-1 (WISP-1/VCAM-1) system in this tumor–bone interaction contributes to human PCa cell motility. In this study, we found that WISP-1 regulates bone mineralization by inducing bone morphogenetic protein-2 (BMP2), BMP4 and osteopontin (OPN) expression in osteoblasts. We also found that WISP-1 inhibited RANKL-dependent osteoclastogenesis. Moreover, osteoblast-derived WISP-1 enhanced VCAM-1 expression in PCa cells and subsequently promoted the adherence of cancer cells to osteoblasts. Furthermore, endothelin-1 (ET-1) expression in PCa cells was regulated by osteoblast-derived WISP-1, which promoted integrin α4β1 expression in osteoblasts via the MAPK pathway. Pretreatment of PCa cells with VCAM-1 antibody or osteoblasts with integrin α4β1 antibody attenuated the adherence of PCa cells to osteoblasts, suggesting that integrin α4β1 serves as a ligand that captures VCAM-1 + metastatic tumor cells adhering to osteoblasts. Our findings reveal that osteoblast-derived WISP-1 plays a key role in regulating the adhesion of PCa cells to osteoblasts via the VCAM-1/integrin α4β1 system. Osteoblast-derived WISP-1 is a promising target for the prevention and inhibition of PCa-bone interaction. Highlights: Osteoblast-derived WISP-1 promotes bone remodeling. Osteoblast-derived WISP-1 promotes VCAM-1 expression in prostate cancer. Prostate cancer cells adhere to osteoblasts via the VCAM-1/integrin α4β1 system. Osteoblast-derived WISP-1 induces increased expression of ET-1 in prostate cancer cells. ET-1 induces integrin α4β1 expression in osteoblasts via the MAPK signaling pathway.